METAMODERNISM AS ALTERNATIVE TO THE “END OF HISTORY” - NEMISHALYAN, ROZA (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
What kind of world do we live in? Since the tragic events of September 11, 2001, the world has changed, a new era has begun, where the cultural, social, economic, technological, political implications of understanding the essence of man changed. Many scientists and thinkers agree with the issue of the end of the post-modern era. Some of them say that post-modern has led to a sudden end due to tangible events of climate change, financial crisis, terrorist attacks, and the digital revolution. However, there is no single answer to the question of what era has come. Some call the contemporary world hypermodern, others auto modern, alter-modern, etc. In 2010 Dutch Timotheus Vermeulen and Robin van den Akken published an article “Notes on Metamodernism”, in which they described modern reality as metamodern, the distinguishing feature of which is oscillation.
Keywords: metamodern, postmodern, capitalism, oscillation, alternative, end of history